Adapting to Another “New Normal”: The Pandemic’s Impact on Generation Z’s Team Dynamics (American Journal of Management, 2024)
The role of teamwork in modern organizations is more crucial than ever. This research investigates whether the COVID-19 pandemic has permanently altered Generation Z’s perceptions and behavior on team projects. A study of graduating seniors at a Southeastern university found decreased team conflicts during and after the pandemic compared to pre-pandemic levels. Task attractiveness and interpersonal cohesiveness declined during COVID-19 but rebounded post-pandemic, though not to pre-pandemic levels. These findings have implications for educational programs, workforce development, and organizational practices aimed at supporting Generation Z’s success and well-being as they transition into their careers.
Keywords: management; teamwork; post-pandemic; conflict management; Generation Z